Enhancement biodegradation of n-alkanes from crude oil contaminated seawater - Zahed, M.A. (2010)
The aim of this research was to optimize bioremediation of seawater samples spiked with 1000 mg/L crude oil for removal of n-alkanes (C12H26 to C34H70). Bioaugmentation experiments were performed at laboratory scale: each bioreactor contained 250 ml dispersed crude-oil-contaminated seawater, indigenous acclimatized microorganism and nitrogen and phosphorus at concentrations based on central composite design (CCD) calculations. Three independent variables, time, nitrogen and phosphorus, were investigated and the experimental data obtained were fitted to a second-order polynomial mathematical model with multiple regressions. The obtained Model F-value of 97.12 and probability F <0.0001 implies the model is significant. Hydrocarbon analyses were carried out using a gas chromatograph equipped with flame ionization detector (GC/FID). During 28 days of experimentation, a maximum of 85.35% total n-alkane removal was observed. Numerical optimization was achieved based on desirability functions. Using 188.71 mg/L nitrogen and 18.99 mg/L phosphorus, design of experiment (DOE) software predicted 91.00% removal. A removal of 92.04% was observed experimentally, in close agreement with the predicted value.